Partial Removal of Phenolics Coupled with Alkaline pH Shift Improves Canola Protein Interfacial Properties and Emulsion in In Vitro Digestibility - Jiang Jiang; Yunqing Nie; Xuemei Sun; Youling L. Xiong (Foods, 2021)
The effect of polyphenol removal (“dephenol”) combined with an alkaline pH shift treatment on the O/W interfacial and emulsifying properties of canola seed protein isolate (CPI) was investigated. Canola seed flour was subjected to solvent extraction to remove phenolic compounds, from which prepared CPI was exposed to a pH12 shift to modify the protein structure. Dephenoled CPI had a light color when compared with an intense dark color for the control CPI. Up to 53% of phenolics were removed from the CPI after the extraction with 70% ethanol. Dephenoled CPI showed a partially unfolded structure and increased surface hydrophobicity and solubility. The particle size increased slightly, indicating that soluble protein aggregates formed after the phenol removal. The pH12 shift induced further unfolding and decreased protein particle size. Dephenoled CPI had a reduced β subunit content but an enrichment of disulfide-linked oligopeptides. Dephenol improved the interfacial rheology and emulsifying properties of CPI. Although phenol removal did not promote peptic digestion and lipolysis, it facilitated tryptic disruption of the emulsion particles due to enhanced proteolysis. In summary, dephenol accentuated the effect of the pH shift to improve the overall emulsifying properties of CPI and emulsion in in vitro digestion.